2020
DOI: 10.1038/s41562-020-0833-x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to untrustworthy websites in the 2016 US election

Abstract: Though commentators frequently warn about “echo chambers,” little is known about the volume or slant of political misinformation people consume online, the effects of social media and fact-checking on exposure, or its effects on behavior. We evaluate these questions for the websites publishing factually dubious content often described as “fake news.” Survey and web traffic data from the 2016 U.S. presidential campaign show that Trump supporters were most likely to visit these websites, which often spread via F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
373
3
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 413 publications
(419 citation statements)
references
References 42 publications
26
373
3
17
Order By: Relevance
“…This is supported by our manipulation check data, which suggests that people in the emotion condition used emotion relatively more than reason, whereas people in the control and reason conditions used reason relatively more than emotion. Such findings are also consistent with literature suggesting that, on average, fake news does not make up a large proportion of people's media diets but rather is particularly consumed and shared by specific political and demographic groups (Guess et al 2019(Guess et al , 2020. Our results are largely consistent with the general idea that fake news belief and consumption may be driven by a small share of individuals sharing specific traits-one of which may be extremely heightened reliance on emotion.…”
Section: Limitationssupporting
confidence: 90%
See 1 more Smart Citation
“…This is supported by our manipulation check data, which suggests that people in the emotion condition used emotion relatively more than reason, whereas people in the control and reason conditions used reason relatively more than emotion. Such findings are also consistent with literature suggesting that, on average, fake news does not make up a large proportion of people's media diets but rather is particularly consumed and shared by specific political and demographic groups (Guess et al 2019(Guess et al , 2020. Our results are largely consistent with the general idea that fake news belief and consumption may be driven by a small share of individuals sharing specific traits-one of which may be extremely heightened reliance on emotion.…”
Section: Limitationssupporting
confidence: 90%
“…Some recent studies have, in contrast, suggested that fears over widespread exposure to and consumption of fake news may be overstated, as fake news accounts for less than half a percent of Americans' daily media diet (Allen et al 2020). However, while similar findings have supported the conclusion that fake news websites make up a small proportion of media diets overall, these studies have also shown that fake news is disproportionately visited by specific groups of people (e.g., supporters of Donald Trump; Guess et al 2020; social media users over the age of 65; Guess et al 2019). Thus, regardless of the impact of fake news on the average Americans' overall media consumption, fake news may still impact the belief in and spread of news in key political and demographic communities.…”
Section: Introductionmentioning
confidence: 97%
“…A related concern is that the intervention could reduce the overall accuracy of people's beliefs given that they typically consume much more information from mainstream sources than from untrustworthy ones (53). To address this concern, we use US Pulse web metering data to estimate the overall change that the intervention would hypothetically induce in people's ability to accurately discern credible news given exposure rates for US participants to different types of news sources (see SI Appendix, section G for details).…”
Section: Discussionmentioning
confidence: 99%
“…We argue that the behavioural sciences should play a key role in informing and designing systematic responses to such threats. The role of behavioural science is not only to advance active scientific debates on the causes and reach of false information [21][22][23][24][25] or on whether mass polarization is increasing [26][27][28] ; it is also to find new ways to promote the Internet's potential to bolster rather than undermine democratic societies 29 . Solutions to many global problems-from climate change to the coronavirus pandemicrequire coordinated collective solutions, making a democratically interconnected world crucial 30 .…”
mentioning
confidence: 99%